(untitled) (CIPEEX, 2022)
OBSTETRIC VIOLENCE IS A CONGLOMERATION OF DISPUTES, NEGOTIATIONS, POWER PROPOSALS, SYMBOLIC AND REAL, CROSSED BY MULTIPLE FACTORS LIKE CLASS, AGE, GENDER; AND OPEN DOORS TO BE QUESTIONED DIFFERENT EDGES, LIKE SO MANY OTHER SOCIAL SIGNIFIERS. (CASTRILLO, 2016). TO ADDRESS THE DETERMINANTS OF OBSTETRIC VIOLENCE IN THE FACE OF THE INNUMERABLE VULNERABILITIES OF WOMEN, WHETHER THEY ARE INHERENT TO PREGNANCY OR BEFORE IT. LITERATURE REVIEW OF 20 ARTICLES RESEARCHED ON THE LILACS, PUBMED AND SCIELO PLATFORMS IN THE ENGLISH, PORTUGUESE AND SPANISH LANGUAGES, EXCLUDING DISSERTATIONS, ACADEMIC ARTICLES AND SYSTEMATIC REVIEWS AND WITH THE AIM OF ANSWERING THE GUIDING QUESTION "WHICH ARE DETERMINANTS OF THE HEALTH-DISEASE PROCESS IN RELATION TO OBSTETRIC VIOLENCE? " THE DETERMINANTS OF OBSTETRIC VIOLENCE IN BRAZIL, INDIA, THE UNITED STATES AND ARGENTINA, VENEZUELA AND SPAIN WERE DISCUSSED, WITH BRAZIL BEING THE COUNTRY WITH THE GREATEST EMPHASIS. THE FACTORS STUDIED AND DISCUSSED WERE AGE, ETHNICITY, SOCIOECONOMIC STATUS OF WOMEN, AND TYPE OF DELIVERY. THE MAIN DISCUSSION IS HOW THESE VARIABLES INTERFERE WITH THE OCCURRENCE OF OBSTETRIC VIOLENCE. THE PREVENTION OF OBSTETRIC VIOLENCE WILL BE EFFECTIVE WHEN THE FACTORS THAT DETERMINE THIS TYPE OF DISCRIMINATION ARE KNOWN AND WHEN THE VULNERABILITIES UNDERLYING THE VIOLATIONS TO WHICH THESE VICTIMS ARE SUBJECTED ARE ADDRESSED. IT IS URGENTLY NECESSARY TO DECONSTRUCT THE VULNERABILITY FACTORS OF THE PAIN-DAUGHTERS SO THAT THESE WOMEN CAN BE AUTONOMOUS AND FREE IN THE VARIOUS OBSTETRIC PROCESSES THAT WILL HAVE TO PASS.